The Effect of Group Counseling Using Cognitive Dispute Techniques To Reduce Academic Procrastination Behavior In Students With Atychiphobia - Sri Puspita Della Aryadi; Ade Chita Putri Harahap (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Academic procrastination is the act of delaying tasks or work that should be prioritized without a clear reason. This study aims to determine the influence and effectiveness of group counseling services using cognitive dispute techniques in reducing academic procrastination behavior in students with atychiphobia. This study employs a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The population in this study consists of all eleventh-grade students at State Senior High School 1 Percut Sei Tuan, with a purposive sampling method yielding a sample size of 14 students divided into an experimental group and a control group. Data collection techniques used an academic procrastination scale questionnaire. Data analysis used a non-parametric test, namely the Wilcoxon Signed Ranks Test, which aimed to determine the difference in academic procrastination levels before and after the service was provided. The results of the study showed that there was an effect of group counseling services using cognitive dispute techniques in reducing academic procrastination behavior in students with atychiphobia. This is indicated by the results of the Wilcoxon Signed Rank Test, with a Z value of -2.371 and Asymp. Sig. (2-tailed) = 0.018, which is smaller than the significance level of 0.05 (p < 0.05) for the experimental group, while there was no significant change in the control group that did not receive any treatment.